Therapeutic intervention with intravenous ferric carboxy-maltose: addressing iron deficiency among heart failure patients - Muneeza Ijaz; Ali Israr Ahmed; Muhammad Ahmad (Journal of the Pakistan Medical Association, 2024)
Dear editor, Heart failure is a debilitating life sentence plagued with multifactorial variables that greatly influence the morbidity and mortality of the patient. Iron deficiency, one of these variables, is a leading contributor to anaemia among individuals with stable chronic heart failure, affecting approximately 30% to 50% of this population irrespective of left ventricular ejection fraction or demographic variables such as gender and race.(1,2) Intriguingly, even among those without overt anaemia, more than 40% display laboratory evidence of depleted iron stores. Moreover, in acute decompensated heart failure (HF), iron deficiency (ID) can be identified in as many as 80% of assessed patients, emphasizing the significance of research initiatives aimed at understanding the underlying cause of ID in HF patients and enhancing their clinical management.(3) A survey conducted in the region of South Asia revealed that 46% of Pakistani heart failure patients and 58.8% of those in India were affected by iron deficiency(4). Implementing simple practices to treat the underlying anaemia can massively improve the quality of life and reduce rehospitalization rates.(1–3,5) Notably, in Pakistan, the rehospitalization rate sits at a staggering 81%. Ferric carboxy-maltose is an intravenous iron formulation which has been extensively explored in clinical studies such as the IRON-CRT, IRONMAN and AFFIRM-AHF trials. The trials displayed promising outcomes with marked improvement in general well-being and physical capacities including 6-minute exercise tolerance as well as lowering the need for hospitalisation independent of baseline haemoglobin levels.(1,2,5) Ferric carboxy-maltose has demonstrated superiority over oral iron supplements and other treatments, such as erythropoietin stimulating medications, making it a recommended and successful alternative for iron deficiency therapy according to both European and American guidelines.(1–3,5) The latest heart failure guidelines emphasize the importance of screening for iron deficiency in every patient diagnosed with heart failure.(2) Unfortunately, the implementation of this practice is not consistently applied in developing countries, as observed in our own experiences in Pakistan. In conclusion, establishing Ferric Carboxy-maltose as the standard treatment for iron deficiency is recommended due to its cost-effective nature and the near instant improvement in patients health and morale. This approach would contribute to a more productive and fulfilling life for patients, even enabling them to regain some level of autonomy in their daily activities. —Continue